Tensile Characteristics of Bio-Composite Material Reinforced with Corn Skin - Jefri Bale; Yeremias Pell; Kristomus Boimau; Boy Bistolen; Dion Rihi (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
The main focus of the present work was to study corn skin as reinforcement of polyester bio-composite (CSPCs). The effect of reinforcement type, i.e. short fibers and discontinuous chips, on the tensile properties was studied. The corn skin materials were chemically treated with NaOH and added as reinforcement of polyester bio-composite using the hand lay-up fabrication method. Tensile tests were carried out according to ASTM D3039. The tensile strength characteristics of stress and modulus showed a different behavior between the two types of reinforcement due to a slight difference in specimen thickness, which affected the calculated stress and modulus values. Furthermore, from a physical properties point of view, the larger surface area of CSC compared to CSF, which still contains a lignin layer after the treatment with NaOH, could decrease the interfacial bonding between polyester as the matrix and CSC as the reinforcement. The tensile damage characteristics showed brittle behavior, propagataing perpendicular to the loading direction. Matrix cracking and interfacial debonding were identified as the main two damage modes of the CSF bio-composite and the CSC bio-composite, where the final failure was dominated by fiber pull out and chip fracture.